2019
DOI: 10.2967/jnumed.119.229187
|View full text |Cite
|
Sign up to set email alerts
|

Matched-Pair Comparison of 68Ga-PSMA-11 PET/CT and 18F-PSMA-1007 PET/CT: Frequency of Pitfalls and Detection Efficacy in Biochemical Recurrence After Radical Prostatectomy

Abstract: 18 F-labeled prostate-specific membrane antigen (PSMA)-ligand PET has several principal advantages over 68 Ga-PSMA-11. The purpose of this retrospective study was to evaluate the frequency of non-tumor-related uptake and the detection efficacy comparing 68 Ga-PSMA-11 PET/CT and 18 F-PSMA-1007 PET/CT in recurrent prostate cancer (PC) patients. Methods: The study included 102 patients with biochemically recurrent PC after radical prostatectomy undergoing 18 F-PSMA-1007 PET/CT imaging. On the basis of various cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
164
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(217 citation statements)
references
References 26 publications
17
164
1
4
Order By: Relevance
“…Recently, a higher number of lesions with increased PSMA-ligand uptake attributed to benign origin were observed in 18 F-labelled PSMA-ligand PET in comparison to 68 Ga-PSMA-11 [26]. However, we do not think that this influences the correct establishment of a prediction nomogram as after adequate reader training, physicians should be well equipped to distinguish likely malignant lesions from those that are most probably benign.…”
Section: Discussionmentioning
confidence: 86%
“…Recently, a higher number of lesions with increased PSMA-ligand uptake attributed to benign origin were observed in 18 F-labelled PSMA-ligand PET in comparison to 68 Ga-PSMA-11 [26]. However, we do not think that this influences the correct establishment of a prediction nomogram as after adequate reader training, physicians should be well equipped to distinguish likely malignant lesions from those that are most probably benign.…”
Section: Discussionmentioning
confidence: 86%
“…For 68 Ga-PSMA-11, the acquisition was performed between 45 and 80 min after injection, whereas 18 F-PSMA-1007 PET/CT was performed 60 min after injection. These uptake periods were derived from the literature (24,34,35). Theoretically, a longer uptake may lead to an improved tumor-to-background ratio (34,35) and result in bias in favor of the tracer for which a longer uptake was applied.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging was done from the tip of the skull to the mid thigh. 68 Ga-PSMA-11 was injected 45-80 min before acquisition started (24), and 18 F-PSMA-1007 was injected as a bolus 60 min before acquisition.…”
Section: Imaging Proceduresmentioning
confidence: 99%
“…The most widely studied is 68 Ga labelled to the small molecular inhibitor PSMA-11 via the HBED chelator ([ 68 Ga]PSMA-11, also known as [ 68 Ga]PSMA-HBED-CC) [13]. A recent meta-analysis published by Perera et al showed on a per lymph node analysis a high sensitivity of 75% and a 99% specificity [14] for [ 68 Ga]PSMA-11 PET/ CT. Because of several advantages of the positron emitter 18 F, 18 F-labelled PSMA ligands ([ 18 F]PSMA-1007, [ 18 F]DCFPYL) were used more and more for imaging instead of 68 Ga-labelled PSMA ligands [15,16].…”
Section: Introductionmentioning
confidence: 99%